Using digital photogrammetry to produce 3D models at prehistoric ditched enclosures: Perdigões as case study. - Caro-Herrero, José Luis; Márquez-Romero, José Enrique; Jiménez-Jáimez, Víctor José (My University, 2014)
Using digital photogrammetry to produce 3D models at prehistoric ditched enclosures: Perdigões as a case study. INTRODUCTION The Perdigões archaeological complex (Reguengos de Monsaraz, Portugal) is a prehistoric site near the Guadiana river, comprising at least 12 ditched enclosures, several hundred pits, an area with megalithic tombs and a set of standing stones (cromeleque). It is located in one of the richest archaeological landscapes of Iberia, with notable examples of Prehistoric monumental architecture such as menhirs and portal tombs (antas). A team from the University of Malaga (Spain) has been carrying out fieldwork in collaboration with the Portuguese entity ERA Arqueologia at the site since 2008. This includes geophysical (2008-2009) and microtopographical (2011) surveys of the whole site, as well as both open-area excavations (2012-2013) and trenches (2009-2010, 2013) in the area surrounding Gate 1. Digital photogrammetry is an inexpensive computerised method that enables the creation of three-dimensional models from photographs using image pattern recognition. The technique can be employed during the process of excavation to better record the archaeological evidence, to generate 3D models of the stratigraphical units and to digitalise singular findings. It is also useful activities aiming to spread knowledge and awareness about the site. In this paper we will describe the basics of the method and its workflows, and three specific applications at Perdigões. Later, we will compare digital photogrammetry with alternative solutions for the digitalisation of cultural heritage, such as LIDAR and total station scanners with LASER. MATERIALS AND METHODS Digital photogrammetry has been utilised in three separate aspects of research at Perdigões: - Generating DTM (digital terrain models) of large excavation areas like that laid out by us around Perdigoes’ Gate 1 (about 1000m2). - Producing 3D models of different excavation trenches made on the site, e.g. a trench over Ditch 1. - Creating models of outstanding findings, like small idols. This task is particularly difficult task because of the small size of the objects. Each of these purposes requires specific modelling techniques and workflows, namely equipment, software programs and techniques like photography, polygons, mesh and texture, all of which will be presented in this paper. RESULTS Digital photogrammetry allowed the generation of a comprehensive model of the large excavation area around Gate 1 of Perdigões that would have been more difficult and expensive using other methods like LIDAR. This excavation recording has been used to obtain paleo-reconstructions of the site. Furthermore, digital photogrammetry has enabled the creation of partial 3D models of the archaeological evidence, which can be later used in the process of analysis and knowledge dissemination. CONCLUSIONS Digital photogrammetry can help archaeologists in many ways, from digitalisation of archaeological contexts and structures in large areas to small artefacts. The resulting models are realistic in terms of looks and textures and can be used in a variety of activities, from recording to interpretation to public access.
Keywords: Arqueología - Aplicaciones informáticas; 3D; Arqueología; Prehistoria; Recintos de fosos